Jogos Pan-Americanos de 2007: uma avaliação social - Behnken, Luiz Mario (2010)
This study aimed to verify to what extent the impacts and legacies of the implementation of the 2007 Pan American Games changed the social conditions and way of use of the urban space in Rio de Janeiro. It was taken into account that the Americas‟ competition is inserted in the application of the global city concepts, since the international sports festivals were transformed into mega events inside the consolidation of the competitive urban planning thought. In order to contextualize this analysis, it was needed a research on the urban history of the host cities at the intersection of two movements: the global city and mega events. Considering the that the decision to conduct the mega event in Rio was taken by the public sphere, as well as its financing, the state spending was analyzed and reclassified according to O‟Connor‟s methodology (1977), and afterwards divided into the functions of accumulation and of legitimacy, in order to identify the advantaged and disadvantaged by effected public policy. The research results showed that there was a deepening of the social and urban inequality and urban, through transfers of public resources for the dominance of private capital.